Mengenal Sastra Anak Melalui Pembelajaran Bahasa Indonesia di Kelas VII dalam kurikulum 2013 Sekolah Menengah Pertama - Rondiyah, Arifa Ainun (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2022)
Learning Indonesian is a learning that has an important role in terms of knowledge, emotions and attitudes. Learning Indonesian with material related to literary works in the form of children's literature. Children's literature is part of the 2013 curriculum in Indonesian language learning. This research method uses literature study as data collection. The results of the analysis of research on children's literature in learning Indonesian in grade VII curriculum 2013 high school, namely children's literature into reading that can stimulate children's imagination according to the end and the child's psyche. Fantasy stories are stories whose plot development uses a causal basis as a form of moral message and combines logic with things that don't make sense. A fable is a traditional story in which the character is an animal about the life of an animal which is intended as a personification of human character that contains a moral message. Witty rhymes are rhymes that aim to entertain and have value or are humorous without offending others and as a means of socializing. The role of children's literature is to become a medium for teachers to introduce good attitudes and behavior and things that are not accepted in society with the characters in fables and fantasy stories. Keywords: Indonesian language learning, children's literature, the role of children's literature